Subcutaneous daratumumab plus standard treatment regimens in patients with multiple myeloma across lines of therapy (PLEIADES): an open‐label Phase II study. (30th July 2020) - Chari, Ajai; Rodriguez‐Otero, Paula; McCarthy, Helen; Suzuki, Kenshi; Hungria, Vania; Sureda Balari, Anna; Perrot, Aurore; Hulin, Cyrille; Magen, Hila; Iida, Shinsuke; Maisnar, Vladimir; Karlin, Lionel; et al.
Summary: Daratumumab is a CD38‐targeting monoclonal antibody approved for intravenous (IV) infusion for multiple myeloma (MM). We describe the Phase II PLEIADES study of a subcutaneous formulation of daratumumab (DARA SC) in combination with standard‐of‐care regimens: DARA SC plus bortezomib/lenalidomide/dexamethasone (D‐VRd) for transplant‐eligible newly diagnosed MM (NDMM); DARA SC plus bortezomib/melphalan/prednisone (D‐VMP) for transplant‐ineligible NDMM; and DARA SC plus lenalidomide/dexamethasone (D‐Rd) for relapsed/refractory MM. In total, 199 patients were treated (D‐VRd, n  = 67; D‐VMP, n  = 67; D‐Rd, n  = 65). The primary endpoints were met for all cohorts: the ≥very good partial response (VGPR) rate after four 21‐day induction cycles for D‐VRd was 71·6% [90% confidence interval (CI) 61·2–80·6%], and the overall response rates (ORRs) for D‐VMP and D‐Rd were 88·1% (90% CI 79·5–93·9%) and 90·8% (90% CI 82·6–95·9%). With longer median follow‐up for D‐VMP and D‐Rd (14·3 and 14·7 months respectively), responses deepened (ORR: 89·6%, 93·8%; ≥VGPR: 77·6%, 78·5%), and minimal residual disease–negativity (10 ‒5 ) rates were 16·4% and 15·4%. Infusion‐related reactions across all cohorts were infrequent (≤9·0%) and mild. The median DARA SC administration time was 5 min. DARA SC with standard‐of‐care regimens demonstrated comparable clinical activity to DARA IV–containing regimens, with low infusion‐related reaction rates and reduced administration time.